Torque ripple reduction of switched reluctance motor using direct instantaneous torque control and adaptive turn‐on technique for electric vehicle applications - Laith Al Quraan; Laszlo Szamel (IET Electric Power Applications, 2023)
Abstract Direct Instantaneous Torque Control (DITC) with an adaptive turn‐on angle technique is presented in this paper to improve the torque ripple of the Switched Reluctance Motor (SRM) for Electric Vehicle applications. Torque ripple suppression is achieved by employing two operating modes during the commutation interval. First, both the outgoing and incoming phase states are modified to track the required torque during the incoming phase's minimum inductance area. As soon as the incoming phase leaves its minimum inductance zone, the outgoing phase is demagnetised, and only the incoming phase state is modified for torque tracking. In addition, a closed‐loop regulator is used to dynamically control the turn‐on angle that drives the incoming current to reach its first peak at the instant of switching between the two operation modes when the rotor and stator poles initiate overlap, thus increasing the motor's efficiency. Simulation results showed that the proposed control method has superior advantages over the traditional DITC and Average Torque Controller. Furthermore, the simulation results were verified experimentally using a four‐phase 4kW, 8/6 SRM prototype.